Visible Light-Triggered Regiodivergent and Enantioselective Alkylation of Glycine Derivatives - Yang, Fuxing; Gong, Lei (Synlett, 2025)
Regiodivergent asymmetric synthesis provides a powerful strategy for generating structurally diverse chiral molecules from common starting materials. However, achieving precise control over both regio- and stereoselectivity in radical-mediated processes remains a formidable challenge, largely due to the transient nature and flexibility of radical intermediates. To tackle this longstanding issue, we have developed a cooperative catalytic platform that integrates photoinduced hydrogen atom transfer (HAT) with chiral copper catalysis. This dual-catalyst system enables regiodivergent and enantioselective C(sp3)–H functionalization of N-aryl glycine derivatives using simple hydrocarbons as alkylating agents. Through systematic modulation of chiral ligands, additives, and other reaction parameters, we have achieved switchable formation of either C(sp3)–C(sp3) or C(sp3)–N bonds, leading to the selective synthesis of C- or N-alkylated products. The reactions proceed with high efficiency (up to 92% yield), excellent regiocontrol (>20:1 rr), and outstanding enantioselectivity (up to 96% ee). Importantly, this methodology facilitates site-selective alkylation of biologically relevant scaffolds and demonstrates tunable regioselectivity under mild photochemical conditions. Thus, it establishes a new paradigm for stereocontrolled bond construction in complex molecular architectures.
Keywords: Regiodivergent synthesis; Asymmetric synthesis; Hydrogen atom transfer; Chiral copper catalysis; C(sp3)–H functionalization